Tanggungjawab Dokter - moh adib (Fakultas Hukum Universitas Darul Ulum, 2012)
The research problem is when does a doctor can be expressed malpractice ?. The purpose of thisstudy was to determine some criteria that must be met in determining cases of malpractice by doctorsin performing profession.The result is that there is a difference between theory and practice. According to the theory to beable to prove the existence of medical malpractice, there are three criteria used are: The requirementfor physicians providing care to the patient, presence of a violation of such obligations, The emergenceof losses as a result. Meanwhile, according to the practice to be declared malpractice should be fourcriteria: existence of a relationship between the rights and obligations of doctors and their clients (duty)?, existence of breach of duty (break of duty), presence of physical loss (damage), There is a causalrelationship ( causation), so that all the elements proved; ie elements of duty, break of duty, demageand causation, it was malpractice.The emergence of accountability to civil doctor when can dibutikan their unlawful acts, in thesense that doctors make mistakes / omissions but errors / omissions that cause harm, such as in errors /omissions by doctors cause injury or handicap something limbs even losses, which inflicts death